Cervicothoracic stab wound trauma: a case report - Ortega Martinez, Rommer Alex (2023)
Cervical trauma by sharp weapon is rare; however, due to the great clinical interest, it can lead to very important complications, such as asphyxia, massive hemorrhage and even death, especially because 10% of traumatic injuries affect the cervical region (zone 1), which, because it contains important organs and vascular bundles, has a mortality rate of 1 to 7%. Thus, we present the clinical case of a 90-year-old female patient with senile dementia, a clinical picture of 1 hour of evolution, with a wound in the right cervical region by a sharp object, with bleeding and local pain, apparently due to self-injury. The patient underwent surgery to remove the sharp object and was managed in the intensive care unit (ICU) for monitoring, presenting an optimal evolution and discharged on the third day; she was subsequently discharged home in good general condition.